2020
DOI: 10.1101/2020.09.01.278382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordination Among Multiple Receptor Tyrosine Kinase Signals ControlsDrosophilaDevelopmental Timing and Body Size

Abstract: Body size and the timing of metamorphosis are two important interlinked life-history traits that define holometabolous insect development. Metamorphic timing is largely controlled by a neuroendocrine signaling axis composed of the prothoracic gland (PG) and its presynaptic neurons (PGNs). The PGNs produce prothoracicotropic hormone (PTTH) that stimulates the PG to produce the metamorphosis inducing hormone ecdysone (E) through activation of Torso a Receptor tyrosine kinase the Receptor Tyrosine kinase and its … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Our results show that JAK/STAT signaling is active in the PG at low levels during normal development. Another study examined JAK/STAT activity in the PG and found in it as well expression of the same 10xSTAT-GFP reporter we used (Pan and O'Connor, 2020). We found, in addition, that pupation is slightly advanced and the size of the ring gland is smaller in multiple conditions of JAK/STAT signaling reduction, including knock down in PG cells of upd3, which a GAL4 expression reporter shows is intrinsically expressed in the ring gland.…”
Section: Discussionmentioning
confidence: 67%
“…Our results show that JAK/STAT signaling is active in the PG at low levels during normal development. Another study examined JAK/STAT activity in the PG and found in it as well expression of the same 10xSTAT-GFP reporter we used (Pan and O'Connor, 2020). We found, in addition, that pupation is slightly advanced and the size of the ring gland is smaller in multiple conditions of JAK/STAT signaling reduction, including knock down in PG cells of upd3, which a GAL4 expression reporter shows is intrinsically expressed in the ring gland.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, IIS activation could prevent starvation-induced autophagy in PG cells, which has been shown to block ecdysone production in condition of a pre-NRC starvation, by shunting cholesterol away from the biosynthetic pathway (Pan, Neufeld, & O’Connor, 2019). Recent evidence suggests that alternative nutrient-independent growth factors such as Jelly-belly (Jeb) can also act on PG cells to stimulate IIS and ecdysone production (Pan & O’Connor, 2020). Jeb and Dilps could constitute separate inputs on ecdysone production, explaining why removal of CC Dilps only affects acceleration upon nutrient restriction but does not delay pupariation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, flies that bear a null mutation for PTTH show delayed development, but are still viable [ 66 ]. In a recent study two additional peptides, jelly belly ( jeb ) and PDGF- and VEGF-related factor 3 ( pvf3 ), were shown to be expressed in PTTH-producing neurons [ 77 ]. When the individual receptors for jeb and pvf3 are knocked down in the PG, animals exhibit a mild developmental delay and increased body size [ 77 ].…”
Section: The First Peptides Shown To Regulate Ecdysone Production Were Discovered In Lepidopteramentioning
confidence: 99%
“…In a recent study two additional peptides, jelly belly ( jeb ) and PDGF- and VEGF-related factor 3 ( pvf3 ), were shown to be expressed in PTTH-producing neurons [ 77 ]. When the individual receptors for jeb and pvf3 are knocked down in the PG, animals exhibit a mild developmental delay and increased body size [ 77 ]. Interestingly, when the receptors for both jeb and pvf3 are knocked down in the PG in a ptth null mutant background, the developmental delay is more prolonged, and there is a larger increase in body size than in animals where only the individual receptors for jeb and pvf3 have been knocked down in the PG [ 77 ].…”
Section: The First Peptides Shown To Regulate Ecdysone Production Were Discovered In Lepidopteramentioning
confidence: 99%
See 1 more Smart Citation